Religious capital and job engagement among Malaysian Muslim nurses during the COVID-19 pandemic - Mukhlis, Hamid; Ibraheem Shelash Al-Hawary, Sulieman; Viet Linh, Hoang; Rasool Hani, Ibrahim; Adnan, Samar (Hervormde teologiese studies, 2022)
Even if religiosity has long been introduced as the major cause for backwardness by anti-religion philosophers, the divine religion has been an important source of value for individuals and society, encouraging them to shape economic and sociocultural outcomes. In this manner, religiosity and religious capital (RC) are the stimuli for society-wide development. Against this background, religion can have positive implications for enriching individual and social economy. Assigning tasks, providing guidance on productivity and more effort, living a purposeful life, establishing effective socio-economic institutions and assessing functional behaviours in organisational settings are accordingly among the ways in which RC induces economic behaviours. On the other hand, job engagement (JE) has been one of the relatively common concepts within the novel approaches to human resource management. Considering employment and the promotion of standard Islamic culture, how religion and JE are associated is thus of utmost importance. Hence, this study aimed to investigate the effect of RC on JE among 2500 Malaysian Muslim nurses working in Kuala Lumpur and Penang hospitals during the coronavirus disease 2019 (COVID-19) pandemic in 2021, as the statistical population selected via random sampling. A standardised questionnaire was also administered as the data collection tool, whose validity and reliability were confirmed. The SPSS and LISREL software packages were further utilised to analyse the data. The study results revealed that RC had a significant positive effect on nurses’ JE in the course of COVID-19 (p = 0.83, t = 11.94).Contribution: The research findings suggest that reinforcing RC in Islamic societies, such as Malaysia, even during the COVID-19 pandemic, affects nurses’ sense of hope, faith and beliefs regarding their capabilities to achieve career success.